Differences in the Characteristics and Factors Associated with Insulin Resistance in Normal Weight and Overweight Polycystic Ovary Syndrome Women - Chimplee, Kaset; Wongpia, Iyara; Paengneewong, Angkana; Charoenpanyavicha, Pitsamai (Biomedical Sciences and Clinical Medicine, 2024)
OBJECTIVE This research aimed to compare clinical and biochemical parameters between normal and overweight-obese polycystic ovary syndrome (PCOS) patients, and to determine the association between insulin resistance (HOMA-IR) and anthropometric, biochemical and hormonal factors in both groups of PCOS. METHODS This study was of a cross sectional design. PCOS was diagnosed using the Revised Rotterdam Criteria 2003. Participants underwent history taking and physical examination. Blood samples were collected for FPG, insulin, lipid profiles, TSH, FSH, LH, SHBG, total testosterone, and free androgen index (FAI). Insulin resistance index was calculated by homeostatic model assessment (HOMA-IR). Clinical and biochemical parameters were compared between both groups of PCOS. Associations between HOMA-IR and anthropometry, biochemistry and hormonal para- meters between groups were determined separately. RESULTS Sixty-four female with PCOS were enrolled. Comparison of biochemical analyses found that the free androgen index was higher and that LH and SHBG were lower in the overweight-obese group. HOMA-IR was greater in the overweight-obese group. In the overweight-obese group, there were statistically significant correlations between the HOMA-IR with the measured BMI, waist circumference, waist-height ratio, HDL, triglycerides, SHBG and the free androgen index. Interestingly, in the normal weight group, only the triglycerides, SHBG and the free androgen indix had a statistically significant correlation with HOMA-IR. CONCLUSIONS There were clear differences in the parameters related to insulin resistance between overweight-obese and normal weight PCOS; however, triglycerides, SHBG, and the free androgen index played a significant role in insulin resistance in both groups of PCOS.